QUEER MATERIALITIES AND INSTAGRAM LIVE INTERVIEWING: COMMUNITY ENTANGLEMENTS - Willcox, Marissa Grace; Hickey-Moody, Anna Catherine (AoIR Selected Papers of Internet Research, 2020)
Digital community making through a live entanglement of the self and social media, offers up new pathways for thinking through human and nonhuman divides. Queer activism and feminist art on Instagram has made way for a reframing of what constitutes a ‘digital community’ (boyd 2011, Baym 2015, Oakley 2018). This paper thinks through the materiality of this feminist activist art community through the method of ‘Instagram live interviewing’. Drawing from a larger project that aims to understand the ways activist art practice on Instagram subverts heterosexual norms and patriarchal representation, we argue that the ‘live’ nature (Back, 2012) of the Instagram live interview (Hickey-Moody and Willcox, 2019) mobilizes a new type of queer materiality. By applying Karen Barad’s (2007) feminist new materialist theory of ‘intra-action’ to Rosi Braidotti's thinking about posthuman experience as intra-acting with aspects of the world that she classifys as non-human (2013), we reconceptualize some of the literature around digital community making to account for the needs of those often left out of heteronormative and mainstream narratives. This entanglement of liveness and intra-action in our methodology explores the feeling of ‘community’ as being a feeling that is central to human subjectivity and experience. Through a lens of queer materiality, we suggest that community can therefore be produced by more-than-human assemblages, and argue that a more nuanced account of digital community making which accounts for live Instagram intra-actions, and human to nonhuman relationality is needed.